2021
DOI: 10.31729/jnma.7063
|View full text |Cite
|
Sign up to set email alerts
|

Injury amongst Medicolegal Cases in Department of Forensic Medicine of a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Victim of injuries presenting to a hospital is a medico-legal issue. So, with medical management, proper documentation of injuries should be done as a legal duty by all physicians attending such cases. The study aims to find the prevalence of injury amongst medicolegal cases inthe Department of Forensic Medicine in a tertiary care centre. Methods: A descriptive cross-sectional study was done amongst 328 medicolegal cases presenting at a tertiary center, from January 2019 to February 2021. Ethical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
4
1
0
Order By: Relevance
“…The present study shows that majority of individual involved in violence are male than female which is also supported various studies (4,7). One of the reasons is men usually being the jobholder and they have to involve in outdoor activities.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study shows that majority of individual involved in violence are male than female which is also supported various studies (4,7). One of the reasons is men usually being the jobholder and they have to involve in outdoor activities.…”
Section: Discussionsupporting
confidence: 91%
“…The study showed that 11.4% of injuries were grievous, 2.9% lives threatening and 85.7% were non-grievous. The result is similar to other studies done in Nepal (7,18). Among all the assaulted patients most of them get discharged after conservative management.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Out of 5140 MLCs, the alleged history of a causative factor was blunt force trauma in more than half (N = 2624; 51.05%) cases, followed by RTA (N = 922; 17.93%) and poisoning (N = 917; 17.84%), respectively (Table VIII). Our findings were similar to the studies reported by references [10], [25]- [27], and [29].…”
Section: Alleged History Of the Causes Of Mlcssupporting
confidence: 93%
“…The average age of the victims was 34.53 years and the median age was 32 years. Our findings were similar to the studies reported by references [1], [3]- [9], [11], [13], [15], [16], [18]- [25], and [27]- [38].…”
Section: Agesupporting
confidence: 92%